2019
DOI: 10.30895/2221-996x-2019-19-2-72-80
|View full text |Cite
|
Sign up to set email alerts
|

DNA and RNA Vaccines: Current Status, Quality Requirements and Specific Aspects of Preclinical Studies

Abstract: This review focuses on DNA and RNA vaccines whose potential use was first considered at the end of the 20th century. However, not a single bacterial plasmid-based or mRNA vaccine has been used since that time in public healthcare for the prevention of infectious diseases. Nevertheless, vaccines containing recombinant nucleic acids as the active ingredient still attract interest due to the possibility of rapid development, low-cost production, safety of the technology and the potential to activate cellular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Compared to conventional protein-based vaccines, DNA vaccines are more stable, economical, easier to manufacture, and safer to handle. The classical methods of vaccine administration are intramuscular, intradermal, and subcutaneous injections, which are primarily targeted to myocytes and keratinocytes, as well as APC [41,42]. It is believed that antigen presentation during DNA vaccination may occur via three possible mechanisms:…”
Section: Dna Vaccinesmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to conventional protein-based vaccines, DNA vaccines are more stable, economical, easier to manufacture, and safer to handle. The classical methods of vaccine administration are intramuscular, intradermal, and subcutaneous injections, which are primarily targeted to myocytes and keratinocytes, as well as APC [41,42]. It is believed that antigen presentation during DNA vaccination may occur via three possible mechanisms:…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…DNA vaccination studies have shown that the activation of CD8+ cytotoxic T lymphocytes is largely dependent on dendritic cells, rather than being induced by somatic cells [41,42,43]. This presentation shapes the appropriate pattern of cytokine regulation of the immune response.…”
Section: Dna Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations